2019
DOI: 10.1016/j.canlet.2018.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive TRPV4 channels stabilize VE-cadherin junctions to regulate tumor vascular integrity and metastasis

Abstract: The transient receptor potential vanilloid 4 (TRPV4) channel is a mechanosensor in endothelial cells (EC) that regulates cyclic strain-induced reorientation and flow mediated nitric oxide production. We have recently demonstrated that TRPV4 expression is reduced in tumor EC and tumors grown in TRPV4KO mice exhibited enhanced growth and immature leaky vessels. However, the mechanism by which TRPV4 regulates tumor vascular integrity and metastasis is not known. Here, we demonstrate that VE-cadherin expression at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
6
31
0
Order By: Relevance
“…VE-cad is a transmembrane glycoprotein that can maintain an intercellular connection and is expressed only in highly aggressive tumors. It has been demonstrated that the downregulation of VE-cad can inhibit VM formation 48. TGF-β1 is a cytokine which is secreted by epithelial cells, macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…VE-cad is a transmembrane glycoprotein that can maintain an intercellular connection and is expressed only in highly aggressive tumors. It has been demonstrated that the downregulation of VE-cad can inhibit VM formation 48. TGF-β1 is a cytokine which is secreted by epithelial cells, macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous injection of Lewis Lung Carcinoma cells in TRPV4 knockout mice leads to increased vascular density, higher vessel diameter, and reduced pericyte coverage, overall resulting in enhanced tumor growth ( Adapala et al, 2016 ). More recently, it has also been shown by the same group that TRPV4 silencing causes a significant decrease in VE-cadherin expression at cell-to-cell junctions, with the subsequent increase in vascular leakage ( Cappelli et al, 2019 ). Accordingly, overexpression or pharmacological stimulation of TRPV4 with GSK1016790A has been shown to lead to a “normalization” of the vascular endothelium, enhancing the permeability of chemotherapeutic drugs, and basically blocking tumor growth ( Adapala et al, 2016 ).…”
Section: Introductionmentioning
confidence: 93%
“…VIP significantly increased the lung metastasis of gastric cancer cells in vivo through the VPAC1/TRPV4/Ca 2+ signaling axis 113 . In vivo angiogenesis assay demonstrated that TRPV4 regulates tumor vessel integrity by maintaining VE-cadherin expression at cell–cell contacts 114 .…”
Section: Influence Of Trpv4 On Tumor Metastasis and Possible Mechanismmentioning
confidence: 99%